ANALYSIS OF LEGAL PROTECTION OF SUKUK HOLDERS AGAINST THE RISK OF ISSUERS THAT EXPERIENCE DEFAULT POSITIVE LEGAL PERSPECTIVE - Maranda Sukma Mufatzizah; Abdul Mujib; Siti Nurchahyanti (Hukum Islam, 2023)
Sukuk provide opportunities for the public to make long-term investments, issuance of sukuk can benefit in proportion to the profit sharing. Thus, there is a need for risk management and legal protection for sukuk holders. This study aims to find out clearly related to the regulations that cover sukuk holders against PT Berlian Laju Tanker (issuer) which has failed to pay its principal funds or margin/fees. The method in this study is normative juridical which is carried out by examining library materials or secondary materials. This study uses a qualitative data analysis method which is presented descriptively, namely by describing a policy related to the analysis of legal protection for sukuk holders against the risk of issuers failing to pay. Based on the findings of this study, investors holding sukuk can learn more about companies that issue sukuk so that it is possible to better evaluate the value of returns and control the risks associated with their ownership. Availability of information aimed at reducing default by issuers and increasing capital market efficiency. This research concludes that PT Berlian Laju Tanker sukuk holders are given two different types of legal protection, namely preventive legal protection and repressive legal protection.